Gender differential secular trend in lifetime smoking prevalence among adolescents: an age-period-cohort analysis - Jun Hyun Hwang; Soon-Woo Park (BMC, 2019)
Abstract Background There has been a gender difference in adolescents' lifetime smoking prevalence trends over the last 10 years. This study aimed to explain the gender differential secular trend in adolescents' lifetime smoking prevalence using age-period-cohort (APC) analysis and suggests possible causes for this trend, including Korean tobacco control policies during the last 10 years. Methods We utilized the 2006-2017 Korea Youth Risk Behavior Web-based Survey enrolling grades 7 to 12. Using year of survey and year of entry into middle school, we classified 859,814 students who had ever smoked into 6 age groups, 12 periods, and 17 school admission cohorts. Using APC analysis with the intrinsic estimator method, the effects of age, period, and school admission cohort on lifetime smoking prevalence were analyzed according to gender. Results Overall, there was a similar tendency of all the three effects on lifetime smoking prevalence between genders: an increasing age effect with grade, negative period effect with survey period, and similar pattern of school admission cohort groups. However, compared to boys, girls experienced reduction in the increasing age effect in the 12th grade, consistent and steeper decreasing trend in the period effect from 2006 to 2016, and shorter and lower school admission cohort effect. Conclusions Gender differential response to chronological changes in lifetime smoking prevalence was measured by the APC effect, which affected the gender differential secular trend in lifetime smoking prevalence. Therefore, considering the APC effect could help us understand the trend in smoking rates, as well as the contextual factors that affect it.